1, 3-Dioxepine and spiropyran derivatives of viomellein and other dimeric naphthopyranones from cultures of Aspergillus elegans KUFA0015 and their antibacterial activity. (January 2021) - Kumla, Decha; Sousa, Emilia; Marengo, Alessia; Dethoup, Tida; Pereira, José A.; Gales, Luís; Freitas-Silva, Joana; Costa, Paulo M.; Mistry, Sharad; Silva, Artur M.S.; Kijjoa, Anake
Abstract: Two undescribed viomellein derivatives, xanthoelegansin and spiroxanthoelegansin, were isolated together with clavatol, sitosteanone, vioxanthin, xanthomegnin, viomellein, rubrosulphin, rubrosulphin diacetate, viopurpurin, ochratoxin A, ochratoxin A methyl ester, ochratoxin B and ochratoxin β, from cultures of the marine sponge-associated fungus Aspergillus elegans KUFA0015. The structures of the undescribed compounds were established based on an extensive analysis of 1D and 2D NMR spectra as well as HRMS data. The structure of xanthoelegansin and the absolute configuration of its stereogenic carbons were confirmed by X-ray analysis. The change in conformation of xanthoelegansin was interpreted using quantum mechanical theoretical calculation data in combination with the observation of the change of the proton signals of the 1, 3-dioxepine ring in 1HNMR spectra at varying temperatures. The mechanisms of the formation of xanthoelegansin and spiroxanthoelegansin from viomellein were proposed. Clavatol, sitosteanone, vioxanthin, xanthomegnin, viomellein, xanthoelegansin, rubrosulphin, rubrosulphin diacetate, ochratoxin A, ochratoxin A methyl ester, ochratoxin B and ochratoxin β were assayed for their antibacterial activity against reference strains and multidrug-resistant isolates from the environment. The tested compounds were also evaluated for their capacity to inhibit biofilm formation in the reference strains. Graphical abstract: Two previously undescribed viomellein derivatives, vioxanthin, xanthomegnin, viomellein, rubrosulphin, rubrosulphin diacetate, viopurpurin, ochratoxins A and B, ochratoxin A methyl ester, and ochratoxin β were isolated from the marine sponge-associated fungus Aspergillus elegans KUFA 0015. The compounds were tested for antibacterial and antibiofilm activities against Gram-positive and Gram-negative bacteria and also multidrug-resistant isolates from the environment. Image 1 Highlights: Aspergillus elegans was isolated from the marine sponge Monanchora unguiculata. Viomellein derivatives, xanthoelegansin and spiroxanthoelegansin were isolated. The compounds were tested for antibacterial and antibiofilm activities. Vioxanthin showed strong antibacterial activity against Gram-positive multidrug-resistant strains tested . Vioxanthin and viomellein at MIC inhibited biofilm formation by E. faecalis and S. aureus .